A new species of fossil guenon (Cercopithecini, Cercopithecidae) from the Early Pleistocene Lower Ngaloba Beds, Laetoli, Tanzania. Issue 163 (February 2022) - Arenson, Julia L.; Harrison, Terry; Sargis, Eric J.; Taboada, Hannah G.; Gilbert, Christopher C.
Abstract: The living guenons (Cercopithecini, Cercopithecidae) are speciose and widely distributed across sub-Saharan Africa but are poorly represented in the fossil record. In addition, the craniodental and skeletal similarity of the guenons has hampered the identification of fragmentary material, likely obscuring the taxonomic diversity represented in the fossil record. Here, we describe a new fossil guenon specimen (LAET 75-3703) from the Lower Ngaloba Beds, Laetoli in Tanzania, dated to ∼1.7–1.2 Ma and preserving the lower face and mandible. Comparison to 278 extant guenon specimens, representing all six extant genera, identified several informative traits for distinguishing between the morphologically similar Chlorocebus and Cercopithecus, and these support the attribution of LAET 75-3703 to Chlorocebus . A discriminant function analysis of seven craniodental indices on a subsample of Chlorocebus and Cercopithecus was robust with an overall correct classification rate of 80.4%, and it classified LAET 75-3703 as a member of Chlorocebus with a posterior probability of 92.7%. LAET 75-3703 shares with Chlorocebus the presence of small 'thumbprint' depressions on the maxilla; a tall, narrow, and diamond-shaped nasal aperture; a relatively longer and shallower face; relatively buccolingually broader molars; and a shallow mandible that decreases in depth posteriorly. In addition, LAET 75-3703 is distinguished from all extant guenons, including other species of Chlorocebus, in having a very small P 3 relative to M 1 area. As such, LAET 75-3703 is assigned to a new species, Chlorocebus ngedere sp. nov. This specimen represents the first cercopithecin from Laetoli, as well as the oldest fossil cercopithecin confidently attributed to a modern genus.